Regional phytoplankton responses to upwelling in the Arabian Gulf and northwestern Arabian Sea adjacent to the Omani coast - Ismail, Kaltham A.; Salim, Mohammed (Frontiers in Marine Science, 2025)
Phytoplankton productivity in the Arabian Gulf is strongly influenced by regional oceanographic processes, yet the specific role of upwelling remains unclear. This study addresses this gap by analyzing seasonal and lagged correlations between Chlorophyll-a (Chl-a) concentrations and Vertical velocity (Wt) during the summer monsoon period (June–September 2018). The results show that in the Iranian regions (I & II), a slight delay in phytoplankton response to upwelling was observed in early summer, with the highest correlation at lag 1 in June (r = 0.80). In contrast, Region III, located in the northwestern Arabian Sea adjacent to the Omani coast, exhibited an immediate response throughout the season, with peak correlations at lag 0 (r = 0.72 in June and 0.67 in July). Stratification and horizontal currents played distinct roles in modulating Chl-a distributions: in Iran, stratification was positively correlated with Chl-a throughout the season (r = 0.37–0.42), while currents showed a consistently negative correlation (r = -0.57 to -0.40). In region III, stratification was negatively correlated with Chl-a in June (r = -0.54), becoming positive in later months (up to r = 0.39), and currents were positively correlated throughout (r = 0.15–0.42). These regional contrasts emphasize the importance of local oceanographic context, with upwelling, stratification, and horizontal transport exerting distinct controls on phytoplankton dynamics in the Arabian Gulf and northwestern Arabian Sea.